Answers

2014-12-08T12:08:28+08:00
4m-6{m+4[m-(m+10)+2]}
Since this involves numerous groupings, first thing to observe and to solve is theINNERMOST quantity.
In this case, the innermost quantity is (m+10).
Since you can't simplify that, proceed by removing the quantity.Since the quantity is denoted by a negative sign outside of it, removing the parenthesis you'll have -(m+10) = -m - 10
4m-6{m+4[m-(m+10)+2]}  = 4m-6{m+4[m-m-10+2]}
Simplify the new grouping
4m-6{m+4[m-m-10+2]} = 4m-6{m+4[-8]}
Removing the [] sign you'll have
4m-6{m+4[-8]} = 4m-6{m-32}
                          = 4m -6m + 192
                          = -2m + 192
------------------------
Therefore the simplified form is -2m + 192
0